Persepsi Dan Harapan Mahasiswa Terhadap Kualitas Pelayanan Pada Perguruan Tinggi ”X” Di Surabaya - V. Ratna Inggawati (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
This research is to see how student assessment of the quality of service Perguruan Tinggi "X" as a whole based on the dimensions of physical evidence (tangible), reliability in delivering services (reliability), responsiveness in providing the service (responsiveness), guarantee (assurance) as well as the ability to give attention sincere customer (empathy). Respondents were drawn 100 students, it has been found that the dimensions of the physical evidence is a dimension that has the greatest negative GAP value and genuine concern dimension is the dimension with the smallest negative GAP. Being indicators that have the biggest GAP value is: Complete Library facilities.